Physicochemical properties and plankton composition of the river Meghna, Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted to assess the physicochemical properties and plankton composition of water from the river Meghna (Shatnol to Chor Alexander) in thirteen (13) sampling spots during the period of July 2014 to June 2015. Ten (three were physical and seven were chemical) physicochemical parameters of water viz temperature (air and water), transparency, dissolved oxygen (DO), free carbon dioxide (Co2), Conductivity, pH, total hardness, total alkalinity and ammonia (NH3), plankton community of both phytoplankton and zooplanktons were studied in aforesaid 13 sampling spots of the river Meghna. Maximum air temperature was recorded 37°C at Ananda Bazar. Maximum water temperature was recorded 30°C at Kaligonj, Chor Ludhua and Chor Alexander area of the river Meghna. Transparency was found minimum 12 cm at Chor Ludhua and maximum 75 cm at Horina Ghat. The concentration of dissolved oxygen was found maximum at Chor Voirabi and Horina Ghat 7.3 mg/l and was found minimum at Kaligonj 3.5 mg/l. Free CO2 was found highest at Kaligonj 17 mg/l and lowest at Horina Ghat 5 mg/l. pH was found ranged from almost neutral to alkaline (Minimum 7.2 to Maximum 9). Total hardness was found highest at Chor Alexander 802 mg/l and lowest at Eklaspur 35 mg/l. Total alkalinity was found highest at Chor Alexander 145 mg/l and found minimum at Madrasa Ghat and Hizla 29 mg/l. Conductivity was found highest at Chor Alexander and Chor Ludhua 1000 ?s/cm. Ammonia concentration was found ranged from 0.00 to 0.03mg/l. The mean contribution of phytoplankton was about 90.5% of the total planktonic organisms and zooplankton contributed the rest. The major groups of phytoplankton were found Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, Euglenophyceae, Myxophyceae and Xanthophyceae. Total 9 genera of zooplankton were identified from four families namely Rotifera with 2 genera, Cladocera with 3 genera, Copepoda with 3 genera and Ostracoda with 1 genus from the selected sampling spots.Asian J. Med. Biol. Res. June 2016, 2(2): 324-331